Realisme Moral dalam Pandangan Ṭabāṭabā’ī (Respons terhadap Natuaralisme, Emotivisme, dan Anti-Realisme Moral) - Basrir Hamdani (ILMU USHULUDDIN, 2020)
The main purpose of this article is to point out Ṭabāṭabā’ī’s metaethical idea, that is moral realism, based on the principle of moral philosophy which found in his theory of I’tibāriyat, a theory of perception dealing with various kinds of perception related to practical action of human being whether individual or social. Departing from many problems related to ontological and epistemological statuses of morality that have not been solved yet by several modern metaethical theories, cognitivism and non-cognitivism, this Ṭabāṭabā’ī’s metaethical idea is considered enable to give alternative solutions by proposing two points as the results of reflection on it that morality in the case of metaethical study is imaginative-cognitive-relative and existent in threefold components (action, pupose, and nature of an actor). The elaboration of this reflection in the same time constitutes a response to those modern metaethical theories especially Naturalism, Emotivism, and Anti-Realism. The method by which the writer presents this article is analytical-critical-comparative method, that is, to analyze every idea or theory of metaethics mentioned and, then, by comparative-critical approach, the writer attempts to provide a response to some claims from Naturalism, Emotivism, and Anti-Realism.